PERBANDINGAN TOTAL ARUS KAS SEBELUM DAN SESUDAH PENERAPAN IFRS SERTA PENGARUHNYA TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG LISTING DI BEI - Onidita Putri, Dekka Rinda (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2014)
IFRS is a quality improvement efforts with the financial statements using the same accounting language that can be used globally in the current era of globalization. The financial statements of cash flows is a financial statement that made reference to describe the condition of investor consideration the companys growth. This study aims to analyze the ratio of total cash flow before and after the application of IFRS as well as finding the total effect of cash flow on stock prices. The data used in this study is a secondary data obtained from the annual financial statements of manufacturing companies listed on the Stock Exchange with sampling using purposive sampling with the period 2008-2011. Variables used total cash flows and stock prices. The analysis technique used is a different test t-test and simple linear regression. The results of hypothesis testing that has been done shows that there is a significant difference between the total cash flow before and after the implementation of IFRS. IFRS can improve the value and quality of financial reports, other than that there is a significant positive influence total cash flow on stock prices. For it for the next researcher who wants to analyze about IFRS, it is advisable to add variables to make it more relevant research results.